Шекспировский канон и современный английский роман. Джон Фаулз о В. Шекспире - Терновая, Т.Ю. (Культура народов Причерноморья, 2004)
The article is devoted to the traditional consideration of John Fowles' works. The writer enjoys a justifiably high standing as both a novelist of outstanding imaginative power and as highly self-conscious 'postmodernist' author who fully registers the artifice inherent literary traditions in the act of writing. John Fowles' essay "The Islands" is an new interpretation of the entirely original plot and problems of the Shakespearean play "The Tempest". The author makes the attempt to give his own seeing of the play conflict, which touches upon the philosophic and aesthetic questions. The article develops the appalling ideas of the literal succession of creative works of John Fowles and William Shakespeare.